Influence of MeV H + ion beam flux on cross-linking and blister formation in PMMA resist - Unai S. (2014)
In soft lithography, a pattern is produced in poly(dimethylsiloxane) (PDMS) elastomer by casting from a master mould. The mould can be made of poly(methylmethacrylate) (PMMA) resist by utilising either its positive or negative tone induced by an ion beam. Here we have investigated the irradiation conditions for achieving complete cross-linking and absence of blister formation in PMMA so that its negative characteristic can be used in making master moulds. PMMA thin films approximately 9 μm thick on Si were deposited by spin coating. The 2-MeV H + ion beam was generated using a 1.7-MV tandem Tandetron accelerator. The beam was collimated to a 500×500 μm 2 cross section using programmable proximity aperture lithography system with a real-time ion beam monitoring system and a high precision current integrator. The irradiated areas were investigated by a standard scanning electron microscope and a profilometer. It was found that both the ion beam flux and the stopping power of the ions in the polymer have a critical influence on the blister formation. © 2012 by Maejo University, San Sai, Chiang Mai, 50290 Thailand.